Serious Game with Augmented Reality - Programming on Indoor/Outdoor systems: A case study on Galeria da Biodiversidade da Universidade do Porto - Diogo Alexandre Silva Teixeira (2021)
Museums are cultural institutions dedicated to preserving and interpreting the primary tangible evidence of humankind and the environment, such as the Natural History Museum in London. Since one of the main goals for museums is to educate the population, engaging visitors is paramount and so ways to grab the attention of visitors are being invented. Furthermore, pervasive gaming offers a way to enhance the experience of a user in any context. By extending the gaming experience to the real world, such as a museum visit, the visitors become more than observers, they become players who interact with the scene around them. However, museums still adopt traditional methods of displaying exhibits, which fail to catch the attention of some visitors, especially when it comes to younger people. In the case of Galeria da Biodiversidade, the showcases displaying leaves do not allow any kind of interaction, failing to attract many visitors. As a consequence, they are less likely to fully experience the museum. Additionally, the connection between the leaves in display and the trees planted outside, on Jardim Botânico, also goes unnoticed, if visitors are not on a guided tour. The aim of this project is to explore methods that connect indoor and outdoor environments, which require different accesses for localization, such as GPS and Bluetooth beacons, while applying game-design elements and game principles. This project explores the gamification of the museum experience, while also drawing a connection between the leaves in the exhibition and their respective trees planted outside of the Galeria da Biodiversidade, on Jardim Botânico, improving both the attractiveness of the exhibit and the knowledge acquired by the visitors. Results will likely increase the engagement with the exhibit, making it a more memorable visit. The proposed approach will be tested in the exposition area of the leaves vitrines in Galeria da Biodiversidade and on the exterior garden of Jardim Botânico da Universidade do Porto.